The Law on Physical Intervention against Offensive Schoolchildren – A Nordic Perspective - Jørn Vestergaard (Naveiñ Reet: Nordic Journal of Law and Social Research)
The article gives an account of the legal framework under Danish law regarding physical interventions against schoolchildren who behave offensively, disruptively, or violently. The law is unclear and incomplete. Thus, teachers lack clear guidelines for adequately handling classroom conflict situations. A regulatory model designed to provide more clarity and uniformity is provided.